CYCLOPIA - A. Khamas‎, W.; A. J. Flaih ‎, A.; A. Abbas, Th. (The Iraqi Journal of Veterinary Medicine, 1987)
Cyclopia is a congenital defect in which the two orkits merge to form a single cavity containing one eye, which is likely to show more or less evidence of its origin by fusion of the right and left optic primordia. It is usually combined with cyclencephaly. It is usually described as synophthalmus.